The secret language of destiny: stress imprinting and transgenerational origins of disease - Zucchi, Fabiola C.; Yao, Youli; Metz, Gerlinde A. (Frontiers in Genetics, 2012)
Epigenetic regulation modulates gene expression without altering the DNA sequence to facilitate rapid adjustments to dynamically changing environmental conditions. The formation of an epigenetic memory allows passing on this information to subsequent generations. Here we propose that epigenetic memories formed by adverse environmental conditions and stress represent a critical determinant of health and disease in the F3 generation and beyond. Transgenerational programming of epigenetic regulation may represent a key to understand adult-onset complex disease pathogenesis and cumulative effects of life span and familial disease etiology. Ultimately, the mechanisms of generating an epigenetic memory may become of potentially promising diagnostic and therapeutic relevance due to their reversible nature. Exploring the role of environmental factors, such as stress, in causing variations in epigenetic profiles may lead to new avenues of personalized, preventive medicine based on epigenetic signatures and interventions.